Ten real‐time PCR assays for detection of fish predation at the community level in the San Francisco Estuary–Delta. (13th August 2014) - Brandl, Scott; Schumer, Gregg; Schreier, Brian M.; Conrad, Jessica L.; May, Bernie; Baerwald, Melinda R.
Abstract The effect of predation on native fish by introduced species in the San Francisco Estuary–Delta (SFE) has not been thoroughly studied despite its potential to impact species abundances. Species‐specific quantitative PCR (qPCR) is an accurate method for identifying species from exogenous DNA samples. Quantitative PCR assays can be used for detecting prey in gut contents or faeces, discriminating between cryptic species, or detecting rare aquatic species. We designed ten TaqMan qPCR assays for fish species from the SFE watershed most likely to be affected by non‐native piscivores. The assays designed are highly specific, producing no signal from co‐occurring or related species, and sensitive, with a limit of detection between 3.2 and 0.013 pg/μL of target DNA. These assays will be used in conjunction with a high‐throughput qPCR platform to compare predation rates between native and non‐native piscivores and assess the impacts of predation in the system.